Charge-Separation in Intermixed Polymer:PC70BM Photovoltaic Blends: Correlating Structural and Photophysical Length Scales as a Function of Blend Composition - Utzat,H; Dimitroy,SD; Wheeler,S; Collado-Fregoso,E; Tuladhar,PS; Schroeder,BC; McCulloch,I; Durrant,JR (JOURNAL OF PHYSICAL CHEMISTRY C, 2017)
A key challenge in achieving control over photocurrent generation by bulk-heterojunction organic solar cells is understanding how the morphology of the active layer impacts charge separation and in particular the separation dynamics within molecularly intermixed donor–acceptor domains versus the dynamics between phase-segregated domains. This paper addresses this issue by studying blends and devices of the amorphous silicon–indacenodithiophene polymer SiIDT-DTBT and the acceptor PC70BM. By changing the blend composition, we modulate the size and density of the pure and intermixed domains on the nanometer length scale. Laser spectroscopic studies show that these changes in morphology correlate quantitatively with the changes in charge separation dynamics on the nanosecond time scale and with device photocurrent densities. At low fullerene compositions, where only a single, molecularly intermixed polymer–fullerene phase is observed, photoexcitation results in a ∼ 30% charge loss from geminate polaron pair recombination, which is further studied via light intensity experiments showing that the radius of the polaron pairs in the intermixed phase is 3–5 nm. At high fullerene compositions (≥67%), where the intermixed domains are 1–3 nm and the pure fullerene phases reach ∼4 nm, the geminate recombination is suppressed by the reduction of the intermixed phase, making the fullerene domains accessible for electron escape.